PENGONTROLAN KETINGGIAN AIR PADA BAK PENAMPUNG BERBASIS NODE MCU - Indrianto Indrianto; Ferry Sudarto; Siti Juhriah Novianty (CCIT Journal, 2018)
This research will discuss a system designed to control water use savings. Because water is one of the natural resources of the non-biological. At this point nearly everyone save or hold water in the sump. But, sometimes the water is sure to be closed or turned off so that the water will be wasted over the limit sump. The existence of thisprototype is no more water is wasted down the drain sump over the limit. As for the circuit system used on the prototype consists of a Water Level Sensor as the water sensor, microcontroller (MCU) as Node, Relay switching as that can control the activeand non-active system running, and Solenoid Valve as a valve that cuts or close the stream when the water height is sufficient. So this system aims to control the height of the water in the sump automatically and control the use of water become more efficient